2019
DOI: 10.3390/ijerph16142459
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Prevalence of Orthorexia Nervosa in a Sample of University Students Using Two Different Self-Report Measures

Abstract: In recent decades, orthorexia nervosa (ON) has increased presence in society. It is related with beliefs and attitudes towards eating and is characterized by an obsessive behavior toward heathy eating. The prevalence of ON has been reported by numerous researchers, with rates varying considerably according to the tool used to evaluate the same parameter. The aim of this study was to compare the prevalence of ON in a single population using two different questionnaires. The test for the diagnosis of orthorexia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
6
23
2
Order By: Relevance
“…In non-representative German samples of varying size, including matched control groups of clinical samples and participants of an online survey, estimates range between 3 and 4% [5,[13][14][15]. These numbers are contrasted by studies from the USA [7], China [9], and Spain [16] that reported rates up to 10% in smaller student samples.…”
mentioning
confidence: 89%
“…In non-representative German samples of varying size, including matched control groups of clinical samples and participants of an online survey, estimates range between 3 and 4% [5,[13][14][15]. These numbers are contrasted by studies from the USA [7], China [9], and Spain [16] that reported rates up to 10% in smaller student samples.…”
mentioning
confidence: 89%
“…The minimal sample size was calculated based on a previous study [35] that showed a correlation coefficient between orthorexia (assessed by the DOS scale) and bulimia (assessed by the EDI scale). Based on a correlation coefficient of 0.195, the minimal sample size calculated was 211 [36].…”
Section: Minimal Sample Size Calculationmentioning
confidence: 99%
“…Numerous researchers have reported the prevalence of ON, with values varying considerably according to the measure used to evaluate the same construct (e.g., ORTO-15 test, the Düsseldorf Orthorexia Scale), the selected population (e.g., clinical versus non-clinical samples), and the nationality [ 13 ]. The prevalence of ON ranges from 1% in the general U.S. population [ 14 ] to much higher percentages, particularly among university students worldwide, e.g., 6.6% in a sample of Polish students [ 15 ], 8% in a sample of U.S. students [ 16 ], and 10.5% in a sample of Spanish students [ 13 ]. It has been suggested that the vast inconsistency was mainly due to the difference of instruments used, but not due to cultural differences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%